Assessment of preclinical pharmacokinetics and acute toxicity of pioglitazone and telmisartan combination - Sengupta, Pinaki Ranjan; Chatterjee, Bappaditya; Pal, Tapan Kumar (Academic Press Inc., 2017)
The prevalence of hypertension is very common amongst the diabetic patients and is reported as the major cause of mortality in diabetes. Pioglitazone reported to have an ability to alter the blood cholesterol level and cardioprotective efficiency along with its antidiabetic activity. Telmisartan, through activation of PPAR-γ receptor exerts insulin sensitizing property in addition to its primary cardioprotective efficiency. Theoretically, a combination of pioglitazone and telmisartan may be beneficial to effectively control the high blood glucose level and management of coexisting cardiovascular complication in diabetes. The aim of this research was to experimentally evaluate the pharmacokinetic interaction of pioglitazone and telmisartan when are coadministered in rat. Pioglitazone and telmisartan were administered orally as a single dose individually and in combination to the rats. The plasma samples of the pharmacokinetic study were analyzed using a validated LCMS method. The acute toxicity of the combination with a high dose in rats was also evaluated as a part of the determination its safety profile. There was no significant change in pharmacokinetic parameters were resulted due to coadministration of pioglitazone and telmisartan in rat. Absence of major toxicological effect supports the safety of the combination in vivo.